(untitled) (Scientific journal of the Fergana State University, 2023)
The article theoretically substantiates the concept of naming the cities of Europe of the XII–XV centuries, in which translation activities were established, as a unified system of «The translation centers of medieval Europe». Based on the analysis of Latin sources on the history of translation, the author concluded that the activities of medieval European translation centers should be divided into 3 stages, from which the first period, covering the XII–XIII centuries, should be evaluated as an early stage of the formation of Arabic studies in Europe.